First molecular characterization of Cryptosporidium in Yemen - Alyousefi, N.A.; Mahdy, M.A.K.; Lim, Yvonne Ai Lian; Xiao, L.; Mahmud, Rohela (Cambridge University Press, 2013)
Cryptosporidium is a protozoan parasite of humans and animals and has a worldwide distribution. The parasite has a unique epidemiology in Middle Eastern countries where the IId subtype family of Cryptosporidium parvum dominates. However, there has been no information on Cryptosporidium species in Yemen. Thus, this study was conducted in Yemen to examine the distribution of Cryptosporidium species and subtype families. Fecal samples were collected from 335 patients who attended hospitals in Sana'a city. Cryptosporidium species were determined by PCR and sequence analysis of the 18 s rRNA gene. Cryptosporidium parvum and C. hominis subtypes were identified based on sequence analysis of the 60 kDa glycoprotein (gp60) gene. Out of 335 samples, 33 (9.9) were positive for Cryptosporidium. Of them, 97 were identified as C. parvum whilst 1 case (3) was caused by C. hominis. All 7 C. parvum isolates subtyped belonged to the IIaA15G2R1 subtype. The common occurrence of the zoonotic IIa subtype family of C. parvum highlights the potential occurrence of zoonotic transmission of cryptosporidiosis in Yemen. However, this postulation needs confirmation with future molecular epidemiological studies of cryptosporidiosis in both humans and animals in Yemen.